KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH PADA UNIT PELAYANAN PAJAK DAERAH CIPAYUNG JAKARTA TIMUR - sabil, sabil (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Advertising Tax one tax that contribute to local revenues is quite influential. Local Tax is divided into two types, namely the Provincial Tax them; motor vehicle tax, a tax transfer tax, fuel tax and district tax including; hotel tax, restaurant tax, entertainment tax, street lighting tax, advertisement tax, property tax and urban, customs prolehan rights to land and buildings, taxes bird nest. The types of advertisement tax that became the object of taxation include: Advertising Billboard Megatron / Videotron / large electronic display (LED), reklamem fabrics, billboards attached, advertisement leaflets, walking billboard, advertisement air and billboards voice, advertisement films, billboards show, Taxes Billboards were the subject of tax is an individual or entity that uses billboards. In the Regional Regulation of advertisement tax bases Lease Value Advertising (NSR) can be determined is calculated based on the following matters; the cost of installation of billboards, the size of billboards maintenance costs, long installation of billboards, the strategic value of the location, the type of advertisement. Additionally advertisement tax revenues each year has increased, so give konrtibusi. Advertisement tax to increase local revenue, in the Regional Tax Services Unit Cipayung, advertisement tax contribution in 2012 was 4.1%, was 4.3% in 2013 and 2014 is 4 , 5% each year showed an increase and for the target and the realization, in 2012 exceeded the target is 48.8%, in 2013 exceeded 21.8%, but by 2014 the target is not reached only 77.6%. Some of which provide the contribution of which in 2012, was 6.7% hotel tax, restaurant tax Ran was 2.5%, 8.3% entertainment tax, water tax land tax 1.4 BPHTB 78.4%. Advertising Tax can be determined by the magnitude of the cost of billboard installation costs, maintenance costs billboards, old installation of billboards, the value of strategic location, and type of advertisement. Keywords: Advertising Tax, Local Revenue